College students' sense of belonging and alcohol use amidst COVID-19: Evidence from a 21-day daily diary study. - Maithreyi Gopalan; Jilli Jung; Chiang Shou-Chun; Ashley Linden-Carmichael; Stephanie Lanza (PLoS ONE)
Objective Alcohol use, combined with the heightened mental health crisis among college students highlighted during the pandemic, remains a significant public health concern. We examine (1) how college students' daily assessed sense of belonging with their institution, a key protective factor for better collegiate mental health, is associated with same-day alcohol-use behaviors (2) and how the associations are moderated by key sociodemographic characteristics relevant to this population (women, minoritized students, first-generation [FG], and students identifying as Lesbian, Gay, Bisexual, Transgender, or Queer [LGBTQ]) amidst COVID-19. Method We used mixed models using data from a 21-day daily diary study of college students (N = 2,012) in Spring 2021. Results Results revealed that on days when students felt more uncertainty about their sense of belonging to their college (i.e., low belonging), they were less likely to drink, and drink less overall. This effect was observed after students were back on campus after pandemic-related college closures ended. Heterogeneity by minoritized student subgroups were also observed. Conclusions College students' sense of belonging continues to be an important psychosocial determinant of health and health behaviors among young adults; at times in unintended ways. This reiterates the importance of examining dynamic relationships between belonging and population health. Public health significance statements: These results provide important insight into the linkages between a key psychosocial factor-students' sense of belonging in college-and their alcohol use patterns amidst COVID-19. Institutional programming and prevention efforts to curb alcohol misuse should be implemented with consideration of how those linkages may differ dynamically considering both between- and within-person variance in belonging.